Pengembangan Multimedia “User Education” untuk Meningkatkan Pemahaman Pemustaka dalam Memanfaatkan Fasilitas Layanan pada Perpustakaan Universitas Pendidikan Ganesha - N P Pramita Utami; I K Agus Sugika Putra; N Angela Datta (ACARYA PUSTAKA, 2017)
AbstractThe aims of this study were to: (1) develop multimedia user education to improve the user understanding in utilizing the facilities services at Undiksha library, (2) determine the quality of multimedia user education based on expert validation, and (3) determine the effectiveness of multimedia user education post-implementation. This research was a multimedia development by adopting a model of Luther. The subjects of this study were user, librarian and programmer, and the research objects were multimedia user education, responses of user, librarian and programmer. Data were collected through questionnaires, interviews and observation. The collected data were analyzed descriptively. This research has successfully developed multimedia user education through six stages, namely, concept, design, material collecting, assembly, testing, and distribution. Based on the results of media experts’ validation and librarians, multimedia user education deserves to be implemented as an instructional tool for user education. Multimedia user education is very effective to be implemented in user education activities with the acquisition percentage of 88.1%. The usefulness of multimedia user education reflected in the increased of understanding, motivation and user attitude to utilize the resources available in the Undiksha library. The multimedia is expected to be served as guidelines in user education at the library of Undiksha.Key words: multimedia, user education, library services